LEGAL ENTITIES AS SUBJECTS OF CRIME (World Bulletin of Management and Law, 2026)
This article addresses the issue of recognizing legal entities as subjects of crime in criminal law. The study analyzes fictional, realist, functional, and institutional theories of the criminal liability of legal entities. It also examines approaches to regulating the criminal liability of legal entities in the legislation of foreign states. Relying on the principles of classical criminal law, the author expresses a position on the issue of directly recognizing legal entities as subjects of crime and substantiates the necessity of developing effective and modern legal mechanisms to combat corporate crime. The article also highlights the advantages and disadvantages of introducing criminal liability for legal entities